On a criterion of rationality for a series in orthogonal polynomials - Buslaev, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We present a criterion of rationality for a function determined by its expansion in a series in orthogonal polynomials. This criterion can be regarded as an analog of the well-known Kronecker criterion of rationality for functions given by power series.